Rural Development Over a Period of Time: a Comparative Study of Nodal and Subordinate Villages. - Gopalappa, D.V. and Gowda, Channaveere (2010)
This paper examines in comparative framework developmental outcomes of two neighbouring villages in Kolar District of Karnataka. One of these villages is characterized by features of a “Nodal village” whereas the other is a “Subordinate Village”. The micro-level study shows that unless proactive intervention is made by civil society organizations and self help groups, developmental resources tend to be cornered by the nodal village.